PERANAN KOMPOS PELEPAH KELAPA SAWIT DENGAN BIOAKTIVATOR MOL POME TERHADAP PENINGKATAN SIFAT BIOLOGI TANAH SUB OPTIMAL - Zainudin Zainudin; Roro Kesumaningwati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Sub-optimal land is a lot of lands that is spread in East Kalimantan. Sub-optimal land conditions that have low biological properties is one of the limiting factors in sub-optimal land use for agricultural cultivation. Available suboptimal lands include Ultisol soil types, Imperata grasslands, and ex-coal mining land. This sub-optimal land requires the identification of biological characteristics before determining how to manage it. The research objective is the identification of microfauna including the total population of microorganisms and the identification of bacteria and fungi.  This research will be carried out for 1 (one) year. This research includes the following steps: Making a solution of POME microorganisms takes 14 days, making oil palm frond compost with POME mole bio activator takes about 1 (one) month, Incubation of sub-optimal ex-soil applied to compost requires 2 weeks, and analysis of the total population of soil microorganisms and identification of bacteria and fungi. The results showed that: 1. Microorganism population in sub-optimal land has increased with the addition of oil palm frond compost with POME bio activator 2. There are six genus of fungi namely Trichoderma, Penicillium, Aspergillus, Clamidiospora, Mucor and Aerobasidium. Treatment f1, f2, and f3 had more varied varieties of fungi compared to f0 (control) which only had three fungi genera, 3. the addition of palm frond compost did not increase the Azotobacteraceae population, even in f1 and f3 treatments decreased.